Knowledge, Politics and Power in Global Health Comment on "Knowledge, Moral Claims and the Exercise of Power in Global Health" - Garrett Wallace Brown (Kerman University of Medical Sciences, 2015)
This article agrees with recent arguments suggesting that normative and epistemic power is rife within global health policy and provides further examples of such. However, in doing so, it is argued that it is equally important to recognize that global health is, and always will be, deeply political and that some form of power is not only necessary for the system to advance, but also to try and control the ways in which power within that system operates. In this regard, a better focus on health politics can both expose illegitimate sources of power, but also provide better recommendations to facilitate deliberations that can, although imperfectly, help legitimate sources of influence and power.